Parables of Un-freedom: Novels about the Spanish Inquisition in post-1956 People’s Poland - Bates, John (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article examines three post-1956 novels ostensibly about the Spanish Inquisition’s activities in Spain at the end of the fifteenth century: Jerzy Andrzejewski’s Ciemności kryją ziemię (The Inquisitors, 1957), Julian Stryjkowski’s Przybysz z Narbony (1978), and Jozef Cepik’s Torquemada (1986). These works are placed in a number of broader contexts: the uses of the historical novel in Poland; post-war Polish censorship discourse about the use of historical analogy to address current social and political problems, a practice which the political authorities sought to restrict; the contemporary critical reception where reviews of each novel are seen as articulating the novels’ fundamental concerns albeit subject to the same censorship restrictions; and ultimately the longestablished tradition of Aesopian writing within Polish literature. The analysis demonstrates the expansion of the space for critical public expression particularly in the Thaw years of 1956-57, and its contraction over time up to the mid-1970s. The rise of an independent publishing network at that point paradoxically both facilitates a more open discussion of the potential meanings of literary texts but equally has to observe censorship proprieties to avoid exposing officially published authors to political sanctions. With the growth of underground publishing, the Spanish Inquisition theme gradually declines in relevance, reflected by the critical marginalisation of Cepik’s novel. Ultimately, the article positions the trend within Macherey’s theory of significant silences within literary works, which permits a refinement of the historically contingent screen and marker that have typically defined Aesopian works. The article presents, with their English translations, hitherto unpublished documents from the Polish Party and Censorship archives, including examples of work confiscated by the censors.